Distinct Patterns of Reduced Prefrontal and Limbic Gray Matter Volume in Childhood General and Internalizing Psychopathology. (November 2017) - Snyder, Hannah R.; Hankin, Benjamin L.; Sandman, Curt A.; Head, Kevin; Davis, Elysia P.
Reduced gray matter volume (GMV) is widely implicated in psychopathology, but scholars have found mostly overlapping areas of GMV reduction across disorders rather than unique neural signatures, potentially due to pervasive comorbidity. GMV reductions may be associated with broader psychopathology dimensions rather than specific disorders. We used an empirically supported bifactor model consisting of common psychopathology and internalizing- and externalizing-specific factors to evaluate whether latent psychopathology dimensions yield a clearer, more parsimonious pattern of GMV reduction in prefrontal and limbic/paralimbic areas implicated in individual disorders. A community sample of children ( N = 254, ages 6–10) was used to evaluate whether GMV reductions could constitute early neural risk factors. The common psychopathology factor was associated with reduced GMV in prefrontal areas (dorsal, orbitofrontal, ventrolateral). The internalizing-specific factor was related to reduced GMV in limbic/paralimbic areas (hippocampus, amygdala, insula). No significant associations were found between GMV and the externalizing-specific factor after accounting for common psychopathology.